Intelligent Sensing, Control and Optimization of Networks - Wen, Guanghui; Fu, Junjie; Zhou, Jialing (Sensors (Basel, Switzerland), 2024)
The development of many modern critical infrastructures calls for the integration of advanced technologies and algorithms to enhance the performance, efficiency, and reliability of network systems [...]